Measured versus predicted resting metabolic rate (RMR) in elite rugby 7s players - Black, K. E.; Sims, S.; Baker, D.; Schofield, K.; McQuillan, J.; Thorpe, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
To estimate the energy needs of an individual an indication of their energy expenditure is required which includes Resting Metabolic Rate (RMR). However, measuring RMR in the field is difficult due to the equipment and strict protocols that need to be adhered to. Therefore, predictive equations have been created to estimate RMR as a baseline measurement for energy needs have been generated. However, the accuracy of these measures amongst elite female rugby players has not yet been assessed. The aim of the present study was to determine the accuracy of commonly used RMR prediction equations compared to the direct measurement of RMR amongst elite female rugby 7s players.